Legal Protection For Unregistered Mark in Indonesia - Dania Agustina; Ratih Kemala (IHSA Institute, 2022)
Mark is a sign that identifies an item. Based on the elements in it, the Mark has a distinguishing power and is used in the context of trading goods or services. In Indonesia, trademarks are protected under the first to file system. This means that a ‘protected mark’ is a mark that has been registered with the Directorate General of Intellectual Property (DJKI) or trademarks declared as ‘well-known mark’. However, currently there are many products whose marks have not been registered with the DJKI. Legal problems often occur when an ‘unregistered mark’ turns out to have similar elements to a ‘well-known foreign marks’ that has been previously registered with the DJKI. This certainly has an impact on the continuity of the mark's business of ‘unregistered marks’. Thus, this journal raises issues, including how the mechanism for registering mark/trademarks is based on the current regulations in Indonesia, and how the protection for the ’unregistered mark’ in Indonesia, with examples of cases of the ‘unregistered mark’ having similar elements to ‘well-known foreign mark’ in Indonesia. The purpose of this study is to find out how the provisions for trademark registration are and to find out how to protect ‘unregistered mark’ in Indonesia. The type of this research is a normative juridical method. The results indicate that mark registration in Indonesia can be carried out in two ways, namely through domestic trademark registration and registration based on the Madrid protocol. Both of these methods now can be submitted through the official DJKI website, namely https://www.dgip.go.id/. As for the ‘unregistered mark’ in Indonesia, there is currently no legal regulation to protect them. The ‘unregistered mark’ has to register through the official website of the DJKI. Regarding if the ‘unregistered mark’ has similarities with a ‘well-known foreign mark’, the owner of the ‘unregistered mark’ must check whether administratively the ‘well-known foreign mark’ has been registered or not, or the protection period has expired, and so on to become an opportunity to be applied for. Even though, in the end was DJKI would decide the decision on the submitted application.